A LOOK AT NURSING MANAGEMENT OF MAJOR EATING DISORDERS IN ADOLESCENTS IN PRIMARY HEALTH CARE: A NARRATIVE LITERATURE REVIEW - Camilo Teixeira, Helton (Health and Society, 2025)
Adolescence is a stage of human development marked by intense biopsychosocial changes, which may increase vulnerability to mental health problems, including eating disorders. In the context of Primary Health Care, these conditions require early, continuous, and coordinated interventions that consider the territory, the family, and the adolescent’s individual characteristics. This study aims to describe, based on the scientific literature, the psychosocial nursing management of eating disorders, with emphasis on Anorexia Nervosa and Bulimia Nervosa among adolescents within Primary Health Care in Brazil. This is a descriptive and reflective narrative literature review, conducted using the Virtual Health Library (VHL), as well as books, technical manuals, and legislation related to mental health, psychiatry, primary health care, and nursing practice. The findings indicate that nurses in Primary Health Care play a strategic role in the early identification, welcoming, and longitudinal follow-up of adolescents with eating disorders, being a central and essential professional in this process. Nursing management should involve physical and mental assessment, mental status examination, and, when necessary, the request for laboratory tests according to Ministry of Health or institutional protocols, in addition to qualified listening, health education, articulation with the psychosocial care network, and shared care with the Primary Health Care team. It is concluded that nursing management of eating disorders during adolescence requires a comprehensive, humanized, and territory-based approach, grounded in bonding, continuity of care, and network articulation. At the same time, gaps in the national scientific production regarding the role of nurses in this field are recognized, reinforcing the need for investments in research and continuing education.